(untitled) (Observatorio Económico, 2014)
The creation of the Sistema de Alta Dirección Pública (ADP, Chile’s senior public management system) has been one of the most significant advances in state modernization in recent years. This institutional framework has made it possible to establish a reasonably transparent and meritocratic process for selecting senior positions in the state administration. Thanks to the new system, a technical stratum has emerged that coexists with political actors and career civil servants: the professional public manager. It comprises 942 first- and second-tier positions in public services covered by this mechanism (110 first-tier positions and 832 second-tier positions. Continue reading...